Synthesis and nitric oxide releasing properties of novel fluoro S-nitrosothiols. Issue 3 (13th December 2018) - Zhou, Yang; Tan, Jinyi; Dai, Yuping; Yu, Yanmin; Zhang, Qi; Meyerhoff, Mark E.
Abstract : A novel family fluoro S -nitrosothiols is developed as NO donors, to stoichiometrically release NO with the clean formation of corresponding disulfides. Abstract : A series of new fluoro S -nitrosothiols is reported as potential nitric oxide (NO) donors. A three-step synthesis and the NO releasing kinetic profiles of these species are presented. The stoichiometric release of NO, with the clean formation of corresponding disulfides, confirms that these new species can facilitate their application as NO donors for various applications including creating novel antimicrobial and thromboresistant fluoropolymer-based medical devices.